2019
DOI: 10.1103/physrevb.99.035436
|View full text |Cite
|
Sign up to set email alerts
|

Van Hove scenario of anisotropic transport in a two-dimensional spin-orbit coupled electron gas in an in-plane magnetic field

Abstract: We study electronic transport in two-dimensional spin-orbit coupled electron gas subjected to an in-plane magnetic field. The interplay of the spin-orbit interaction and the magnetic field leads to the Van Hove singularity of the density of states and strong anisotropy of Fermi contours. We develop a method that allows one to exactly calculate the nonequilibrium distribution function for these conditions within the framework of the semiclassical Boltzmann equation without using the scattering time approximatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…From the properties of energy spectrum which have been discussed in Sec. III some general conclusions related to isoenergetic contours follow: 1) There are no more when two separate contours for given energy E. At fixed energy E magnetic field moves the energy of branch contact E 0 (11) and energies of critical points (25) resulting in Lifshitz electron transition of both types - (1); ϕ h = π, blue dashed contours (2). b) Isoenergetic contours at and for the energy corresponding to the minimum of the parabola (11) ǫ min cont = E = 0.0868: h = 0.3, red shortdashed contour (1); h = 0.5, solid contour (2); h = 0.7, blue long-dashed contours (3).…”
Section: Isoenergetic Contoursmentioning
confidence: 96%
See 2 more Smart Citations
“…From the properties of energy spectrum which have been discussed in Sec. III some general conclusions related to isoenergetic contours follow: 1) There are no more when two separate contours for given energy E. At fixed energy E magnetic field moves the energy of branch contact E 0 (11) and energies of critical points (25) resulting in Lifshitz electron transition of both types - (1); ϕ h = π, blue dashed contours (2). b) Isoenergetic contours at and for the energy corresponding to the minimum of the parabola (11) ǫ min cont = E = 0.0868: h = 0.3, red shortdashed contour (1); h = 0.5, solid contour (2); h = 0.7, blue long-dashed contours (3).…”
Section: Isoenergetic Contoursmentioning
confidence: 96%
“…from which an interesting observation follows: at E = E 0 the extremal radii of the contours k (1,2) + = 2λ (1,2) , for whichλ (1,2) = 0, give energies (25) and positions (22) of critical points on total surfaces ǫ = ǫ 1,2 .…”
Section: Isoenergetic Contoursmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] A method allowing to solve this problem in the semiclassical approximation for low temperatures and elastic scattering of electrons by impurities with a short-range potential was developed in the article. [17] The point is that the integral kinetic equation is the Fredholm integral equation with a degenerate kernel. Therefore, it reduces to an algebraic one and can be exactly solved.…”
Section: Introductionmentioning
confidence: 99%
“…This coupling spin-splits the dispersion curve into the upper and lower helicity bands. It was found that in the low-density regime when only the lower band is filled, the impurity-related resistivity exhibits an unconventional electron-density dependence [11][12][13] . Apparently, this system is not Galilean-invariant and is described at the same time by a minimum number of independent parameters.…”
mentioning
confidence: 99%